Beyond surface dose: subcutaneous dose escalation underlies TomoTherapy’s skin toxicity in breast radiotherapy - Xue, Jiao; Zhao, Wenjun; Wu, Chenchen (Frontiers in Oncology, 2026)
PurposeTo elucidate the dosimetric mechanisms underlying the increased incidence of acute radiation dermatitis associated with Helical TomoTherapy (TOMO) compared to Volumetric Modulated Arc Therapy (VMAT) in whole-breast irradiation.Methods and materialsA retrospective analysis included 40 patients with right-sided breast cancer receiving hypofractionated whole-breast irradiation (40 Gy/15 fractions), evenly matched between VMAT (Elekta Synergy) and helical TomoTherapy (TOMO) groups. Skin dose was evaluated using a multi-parametric approach: 1) Dose Surface Maps (DSM); 2) a novel 5-mm thick PTV-projected adjacent superficial tissue (P-PAST) structure; and 3) equivalent dose in 2-Gy fractions (EQD2, α/β=10). Clinical skin toxicity was graded per RTOG criteria.ResultsClinically significant (Grade 2-4) acute skin toxicity was substantially more frequent with TOMO (70%) than with VMAT (30%, p=0.026). DSM showed TOMO produced a more confined high-dose region on the skin surface compared to VMAT. However, TOMO delivered significantly higher physical and biologically effective doses to the subcutaneous P-PAST region: mean EQD2 was 44.47 ± 1.33 Gy vs. 42.12 ± 0.76 Gy for VMAT (p<0.001). D2cc and maximum dose EQD2 were also elevated in the TOMO group.ConclusionsThe heightened skin toxicity with TOMO is not predicted by conventional skin surface dose metrics but is explained by a significant dose escalation within the subcutaneous P-PAST region. Plan evaluation for TOMO should incorporate volumetric dose assessment of the dermal compartment to mitigate toxicity.